From caterpillar to butterfly - Legg, Gerald; Scrace, Carolyn; Salariya, David (New York : F. Watts, 1998)
Large illustrations and simple text describe how caterpillars become butterflies.
"First published in Great Britain"--P. facing t.p.
"An SBC book"--P. facing t.p.
Includes index.
L.A. Recommended Foreign Language
2.8
K-3
Keywords: Butterflies -- Life cycles -- Juvenile literature; Butterflies; Caterpillars; Metamorphosis; Butterflies; Caterpillars; Metamorphosis